Identification and Ranking of Ethical Human Resources Management Components in Payam Noor University - Saeid Besharati Kivi; Hamid Taboli; Zahra Forotani; Naser Barkhrordar (پژوهش‌های مدیریت عمومی)
Abstract The purpose of the current research is to identify and rank the components of ethics-based human resource management at Payam Noor University. The research method is applied in terms of purpose and mixed (qualitative-quantitative) in terms of data type with an exploratory approach. The identified factors and components were measured by experts' opinions and based on the fuzzy analytic hierarchy process (FAHP) model, the factors were analyzed and combined and finally prioritized. The statistical population in the qualitative part of the study included 15 experts and managers with expertise in human resource management who were selected non-probably and judgmentally and the required information was collected from them using the Delphi method. The fuzzy analytic hierarchy process (FAHP) model was used to analyze the data and finally the components were confirmed in the form of 6 components and 37 indicators. Based on the findings, these components include: equality and development, self-efficacy and self-control, technical-specialized factors, professional perfection, stakeholder interests, and competitive content production. The results show that human resource management, using ethical approaches, can guide employee attitudes and behaviors and optimally perform its tasks and goals in a competitive world.Introduction Sectoralism, inconsistency and inconsistency in ethics between the elements of human resources management, weak education and training of ethics-oriented human resources, lack of a comprehensive and approved ethics-oriented plan at the national level, lack of necessary executive guarantees in some laws and executive methods and Also, the conducted research shows that we are facing a lack of theory, research and models in the field of ethical human resource management in higher education and universities. Therefore, this research aims to investigate and identify the components of ethics-oriented human resources management and prioritize them in order to answer the question that what are the components of ethics-oriented human resources management in Payam Noor University? has investigated the issue.Case study The statistical population of the research includes all the books, researches and articles related to the research subject and expert professors and experts in the field of professional ethics and the academic staff of Payam Noor University, sampling in this research was done in a targeted and accessible way. Was. Because the sample size in the research Quality does not have a specific amount and number, and the number of samples is based on the amount of information available comes and reaches saturation of information is determined.Materials and Methods To determine the sample size, a targeted method was used. A semi-structured interview was used to collect data. In order to analyze and analyze data to prioritize components and indicators, a combination of decision-making methods is used in conditions of uncertainty, and finally weighting of components is done using Buckley's geometric techniques in comparisons. to be Fuzzy pairing was performed. Due to the hierarchical nature of the research factors, the hierarchical process method was used in the Fuzzy AHP environment.Discussion and Results After confirming the components by experts, they were finally approved in the form of 6 components and 37 component indicators. To measure the reliability, the agreement method between two coders was used, and the result indicates 85% agreement between the two coders. Based on the findings, these components include: equality and development, self-efficacy and self-control, technical-expert factors, professional perfection, interests of stakeholders and competitive content production.ConclusionAccepting any role entails responsibilities, and fulfilling these responsibilities requires observing ethical aspects. Teaching is a profession that has a moral nature. Dealing with teaching ethics has been given attention in recent decades in most countries of the world and the basics of teaching ethics and teaching principles have been compiled in the form of professional ethics codes and professionalism standards. The results of the research showed that the most prominent component of human resource management is ethics-oriented respect for equality and development in Payam Noor University. Justice in ethics in the term means putting everything in its proper place and giving the right as much as it deserves.